Individually tailored dosage regimen of full-spectrum Cannabis extracts for autistic core and comorbid symptoms: a real-life report of multi-symptomatic benefits - Montagner, Patrícia Soares Silva; Medeiros, Wesley; da Silva, Leandro Cruz Ramires; Borges, Clarissa Nogueira; Brasil-Neto, Joaquim; de Deus Silva Barbosa, Vinícius; Caixeta, Fabio V.; Malcher-Lopes, Renato (Frontiers in Psychiatry, 2023)
Autism Spectrum Disorders (ASD) may significantly impact the well-being of patients and their families. The therapeutic use of cannabis for ASD has gained interest due to its promising results and low side effects, but a consensus on treatment guidelines is lacking. In this study, we conducted a retrospective analysis of 20 patients with autistic symptoms who were treated with full-spectrum cannabis extracts (FCEs) in a response-based, individually-tailored dosage regimen. The daily dosage and relative proportions of cannabidiol (CBD) and tetrahydrocannabinol (THC) were adjusted based on treatment results following periodic clinical evaluation. Most patients (80%) were treated for a minimum of six months. We have used a novel, detailed online patient-or caregiver-reported outcome survey that inquired about core and comorbid symptoms and quality of life. We also reviewed patients' clinical files, and no individual condition within the autistic spectrum was excluded. This real-life approach enabled us to gain a clearer appraisal of the ample scope of benefits that FCEs can provide for ASD patients and their families. Eighteen patients started with a CBD-rich FCE titrating protocol, and in three of them, the CBD-rich FCE was gradually complemented with low doses of a THC-rich FCE based on observed effects. Two other patients have used throughout treatment a blend of two FCEs, one CBD-rich and the other THC-rich. The outcomes were mainly positive for most symptoms, and only one patient from each of the two abovementioned situations displayed important side effects (one who has used only CBD-rich FCE throughout the treatment, and another who has used a blend of CBD-Rich and THC-rich FCEs.Therefore, after FCE treatment, eighteen out of twenty patients showed improvement in most core and comorbid symptoms of autism, and in quality of life for patients and their families.For them, side effects were mild and infrequent. Additionally, we show, for the first time, that allotriophagy (Pica) can be treated by FCEs. Other medications were reduced or completely discontinued in most cases. Based on our findings, we propose guidelines for individually tailored dosage regimens that may be adapted to locally available qualified FCEs and guide further clinical trials.